Sexual Dimorphism in Diet Preference in the Green Paddy Frog (Hylarana erythraea) - Ting, Li Jie (Universiti Malaysia Sarawak (UNIMAS), 2022)
The diet of Hylarana erythraea was studied at the lakes of East Campus, UNIMAS, Kota Samarahan, Sarawak, where surveys were done between 21 February to 19 April 2022. A total of 47 frogs were collected, examined, and flushed to access their stomach contents and released. There is lack of information on possible relationship between sexual dimorphism and their diet. This study aims to determine the diet preferences of two sexes and to observe the effects of sexual dimorphism in body size on the diet of the target species. The dietary analysis was carried out using the stomach flushing technique on metamorphosed frogs obtained in the field. The diet of the green paddy frog comprised of 54.65% from 12 prey orders of insects, 15.12% of Araneae, 9.30% of Gastropda and 1.16% of Chilopoda. Based on percentage of prey occurrence, prey volume and number, the most important prey categories between both sexes were Araneae, Insecta (Hymenoptera, Diptera and Orthoptera). There are significant differences in prey quantity and prey composition between males and females, prey length increased significantly with snout-vent length (SVL). The increase in prey length with SVL was likely due to avoidance of intraspecific competition, sexual selection as it favoured larger females for higher fecundity. With little known about the ecology of the species and lack of information on its prey composition and prey types, this study generates new knowledge and understanding on theo feeding behaviour of the species.